American College of Clinical Pharmacy White Paper. Cultural Competency in Health Care and Its Implications for Pharmacy Part 3B - O’Connell, Mary Beth (2013)
The Institute of Medicine has stated that greater diversity within health care professionals leads to improved patient outcomes. Therefore, greater diversity within academia and student bodies is required to create future diverse health care professionals. Cultural sensitivity is required from recruitment to physical environment for administrators, faculty, staff, and students. University, college, and department recruitment, search committees, hiring practices, and admissions policies and procedures need to be assessed to determine whether they reflect the applicant pool and patient populations in their regions and whether they are culturally sensitive to a wide variety of cultures. The mission, vision, policies, procedures, curriculums, and environments should also be created or reviewed, modified, and/or expanded to ensure that no administrator, faculty member, staff member, or student is discriminated against or disadvantaged because of cultural beliefs or practices. In addition to discussing the interplay between cultural sensitivity and academic policies, procedures, and environments, this article briefly discusses specific cultural issues related to religion, spirituality, race, ethnicity, gender, age, marital status, veterans, physical, mental, and learning disabilities, and sexual orientation diversity.